Elmet - Mozley, Fiona (JM Originals, 2017)
"Cathy and Daniel live in the remote woods of Yorkshire with their gentle brute of a father, a former enforcer who now wants only to be left alone to raise his children. But when a powerful landowner shows up on their doorstep, a chain of violent events is set in motion"--